Adolescentes com infecção do trato genital inferior por papiloma vírus humano: tratamento e seguimento - Derchain, Sophie Françoise Mauricette; Silva, Marcus Henrique Buzanelli Borges da; Lima Júnior, José Alaércio de Toledo (Brazilian Journal of Sexually Transmitted Diseases, 1996)
To corelate thc patients clinicai cure rate, the compliance of treatment, therapeutic methods, age, hystological diagnosis, smoking and pregnancy in teenagers with clinicai and subclinical human papillomavirus lower tract infection (HPV). lt was evaluated clinicai notes of 183 subjects attended at the Cervical Pathology clinic in the Women Health Center-University of Campinas (CAISM/UNICAMP) from September, 1990, to Fcbrual)’, 1992. The treatmcnt methods was: electocauterization for cexvical and well localizated lesions in vagina or vulva and chemiocauterization with local 5% 5-fluoro-uracil for disscminated micropapilar and aceto-white lesions by the patients at home. 57 patients attended under two consultations and it was considered abandorunent. ln the patients up two cons u ations was higher thc cure rate when highcr the compliancc rate and follow-up. The most frcquently therapeutic mcthod utilizatcd was clectrocauterization associated or not with 5-fluro-uracil. The clilúcal response ranged 50% to 88% with regareis to the treatment methods and the worst results were observed with 5-fluoro-uracil, highlited the dificulty in treat disseminated lesions. Age and smolcing were not correlated with clinicai cure, but pregnant patients in the diagnosis timing prcsented higher spontaneous cure aftcr detive!)’ It was concluded that the compliance rate was low in teenagers, the higher treatment clinicai response rate presented in localizated lesions and pregnants patients must be evaluated after delivel)’ fw treatment.